ANALISIS SEMIOTIKA TEORI UMBERTO ECO DALAM SASTRA LISAN LAMPUNG - Aulia Yunisa; Naila Agustin; Nova Lisna; Zahra Adellia Dewi Jimny (Wiyata Budaya: Jurnal Pendidikan Dalam Konteks Humaniora, 2025)
Lampung oral literature is a form of cultural expression that is passed down from generation to generation through oral traditions such as sagata and ringget. This study aims to examine the symbolic meaning in the two literary works using Umberto Eco's semiotic approach. Eco views text as an open text, namely a text that is open to various interpretations according to the social, cultural, and experience backgrounds of the reader. The work of sagata Merantau represents a narrative of social suffering through symbols of alienation, economic struggle, and longing for one's hometown. Meanwhile, ringget conveys social criticism, love, and life values ​​through irony, metaphor, and idioms typical of Lampung culture. The results of the analysis show that the signs in both texts are not singular, but rather plural, ideological, and contextual. Lampung oral literature, in this case, is not only a means of entertainment or emotional expression, but also a space for the production of cultural meaning, representation of collective identity, and reflection of the social dynamics of society. Sastra lisan Lampung merupakan wujud ekspresi budaya yang diwariskan secara turun-temurun melalui bentuk tradisi lisan seperti sagata dan ringget. Penelitian ini bertujuan mengkaji makna simbolik dalam dua karya sastra tersebut menggunakan pendekatan semiotika Umberto Eco. Eco memandang teks sebagai open text, yakni teks yang terbuka terhadap berbagai interpretasi sesuai latar belakang sosial, budaya, dan pengalaman pembaca. Karya sagata Merantau merepresentasikan narasi penderitaan sosial melalui simbol-simbol keterasingan, perjuangan ekonomi, dan kerinduan kampung halaman. Sementara itu, ringget menyampaikan kritik sosial, cinta, dan nilai kehidupan melalui ironi, metafora, dan idiom khas budaya Lampung. Hasil analisis menunjukkan bahwa tanda-tanda dalam kedua teks tidak bersifat tunggal, melainkan bersifat plural, ideologis, dan kontekstual. Sastra lisan Lampung, dalam hal ini, bukan hanya sebagai sarana hiburan atau ekspresi emosional, tetapi juga sebagai ruang produksi makna budaya, representasi identitas kolektif, dan refleksi dinamika sosial masyarakat.